Bioefficacy of some newer insecticides against cabbage butterfly, Pieris brassicae in cabbage - Chandi, Ravinder Singh; Suri, K S (Indian Journal of Plant Protection, 2020)
Newer insecticides like novaluron 10 EC @ 250, 312.5 and 375 ml ha-1, spinosad 2.5 SC @ 600 ml ha-1, indoxacarb 15.8 SC @ 500 ml ha-1 and flubendiamide 480 SC @ 75 ml ha-1 were evaluated for their efficacy against P. brassicae and compared with conventional insecticides like quinalphos 25 EC and endosulfan 35 EC @ 1000 ml ha-1 and Bt biopesticides, Dipel and Halt. The pre-treatment population of P. brassicae larvae varied from 6.20 to 7.10 and 6.80 to 7.60 larvae/plant during 2010 and 2011 crop seasons, respectively. In 2010, lowest P. brassicae population was observed in novaluron @ 375 ml ha-1 while during 2011, it was lowest in flubendiamide @ 75 ml ha-1 after 3 days of spray. After 7 and 10 days of spray, lowest larval population was observed in novaluron @ 375 ml ha-1 during both the years. Yield of cabbage heads was significantly higher in treated plots than in the untreated control. Cabbage head yield during 2010 and 2011 was highest in plots treated with novaluron @ 375 ml ha-1 (171.75 and 210.82 q ha-1, respectively) with maximum of 16.05 and 45.39 per cent yield increase over the control, respectively. Overall, the study revealed that the newer insecticides such as novaluron, spinosad, indoxacarb and flubendiamide can be used for the management of P. brassicae on cabbage.